Reduction of atherosclerosis in apolipoprotein E knockout mice by activation of the retinoid X receptor - Claudel, Thierry (The National Academy of Sciences, 2001)
A common feature of many metabolic pathways is their control by retinoid X receptor (RXR) heterodimers. Dysregulation of such metabolic pathways can lead to the development of atherosclerosis, a disease influenced by both systemic and local factors. Here we analyzed the effects of activation of RXR and some of its heterodimers in apolipoprotein E −/− mice, a well established animal model of atherosclerosis. An RXR agonist drastically reduced the development of atherosclerosis. In addition, a ligand for the peroxisome proliferator-activated receptor (PPAR)γ and a dual agonist of both PPARα and PPARγ had moderate inhibitory effects. Both RXR and liver X receptor (LXR) agonists induced ATP-binding cassette protein 1 (ABC-1) expression and stimulated ABC-1-mediated cholesterol efflux from macrophages from wild-type, but not from LXRα and β double −/−, mice. Hence, activation of ABC-1-mediated cholesterol efflux by the RXR/LXR heterodimer might contribute to the beneficial effects of rexinoids on atherosclerosis and warrant further evaluation of RXR/LXR agonists in prevention and treatment of atherosclerosis.